Application Of The Inquiries Approach To Improve Social Science Learning Outcomes In Grade VI Class Students Of SDN 1 Poasia - Uddin Uddin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aimed to improve the learning achievement of Social Sciences in grade VI C. State Elementary School 01 Poasia through an inquiry approach. This research is classified as Classroom Action Research (CAR) with an inquiry approach in improving the learning outcomes of Class VI students in Social Sciences. C. State Elementary School 01 Poasia. To answer the problems of this research, several factors will be examined, namely as follows: Student Factors Understanding and mastery of the learning materials presented or studied. The abilities and skills of students in applying learning models/approaches in their studies. Teacher Factors This factor relates to learning tools and other facilities such as student books and student activity sheets, according to student competencies. Data analysis in this study was carried out during and after data collection. Data analysis was carried out by comparing the results of observations, interviews, field notes with indicators at the reflection stage and research cycle. That learning achievement in the field of Social Sciences in class VI C Elementary School 01 Poasia can be improved by applying an inquiry learning approach.